Μ‐Conotoxin KIIIA peptidomimetics that block human voltage‐gated sodium channels. Issue 1 (24th October 2020) - Knuhtsen, Astrid; Whiting, Rachel; McWhinnie, Fergus S.; Whitmore, Charlotte; Smith, Brian O.; Green, A. Christopher; Timperley, Christopher M.; Kinnear, Kenneth I.; Jamieson, Andrew G.
Abstract: Peptidomimetics designed to target voltage‐gated sodium channels have attracted significant attention as potential analgesics. However, voltage‐gated sodium channel (VGSC)‐blocking activity of these compounds has mainly been assessed using rat and/or mice homologs. In this study, we developed a novel series of conformationally constrained peptidomimetic analogues of the μ‐conotoxin KIIIA and assessed their activity against human VGSCs. Two of the mimetics block the currents of hNav 1.4 and hNav 1.6 channels. NMR derived structures of the mimetics provided excellent insight into the structural requirements for bioactivity. A lactam‐constrained analogue, previously reported to be active in mice, did not block the corresponding human VGSC. This work highlights important differences in VGSCs between species and validates the potential of peptidomimetics as human analgesics. Abstract :